2014
DOI: 10.9755/ejfa.v26i5.16365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methyl Testosterone (17?-MT) on the phenotype, bioindices and<br>gonads of adult male dwarf Gourami (Colisa lalia)

Abstract: The effect of different concentrations of synthetic androgen 17α-methyl-testosterone (MT) on the adult fish, Colisa lalia was studied in the present investigation. It was found that fishes fed with homogenous mixture of the hormone in ethyl alcohol, exhibited phenotypically, morphometric, gonadal changes and differences in GSI value. Significant differences for length, weight, body color and GSI values were observed between hormones treated and control groups. Fishes fed with hormonal doses of 10 and 15 mg/Kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…Fish groups fed 17α-MT hormone had a better growth rate. These results are in agreement with the studies on Labidochromis caeruleus (see Karsli et al 2018), Oreo-chromis andersonii (see As et al 2012), O. niloticus (see Greisy and Gamal 2012;Ajiboye et al 2015), and Trichogaster lalius (see Biswas et al 2014). However, other studies reported that the hormone treatment negatively affected growth and development in a dose-dependent manner in zebra cichlids (George and Pandian 1996), Betta splendens (see Kirankumar and Pandian 2002), and O. niloticus (see Sreenivasa and Prabhadevi 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Fish groups fed 17α-MT hormone had a better growth rate. These results are in agreement with the studies on Labidochromis caeruleus (see Karsli et al 2018), Oreo-chromis andersonii (see As et al 2012), O. niloticus (see Greisy and Gamal 2012;Ajiboye et al 2015), and Trichogaster lalius (see Biswas et al 2014). However, other studies reported that the hormone treatment negatively affected growth and development in a dose-dependent manner in zebra cichlids (George and Pandian 1996), Betta splendens (see Kirankumar and Pandian 2002), and O. niloticus (see Sreenivasa and Prabhadevi 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Contrarily, Pandian and Sheela (1995) found that hormone treatment shortened reproduction maturity period of P. sphenops. Similarly, the best GSI in C. lalia was obtained in 17α-Mt hormone-treated group (Biswas et al, 2014).…”
mentioning
confidence: 76%
“…In a study conducted with Colisa lalia (Dwarf gourami) species, Biswas et al (2014) applied three different doses (5, 10, 15 mg kg -1 ) of 17α-Mt hormone and reported the best growth in 10 mg kg -1 hormone-treated group. In another study conducted with Oreochromis niloticus (Nile tilapia), Values (mean ± standard error of means for triplicates) with different superscripts in the same row are significantly different (one-way ANOVA and Fisher's multiple-range test, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the aforementioned Swordtail studies, research on the effects of MT in adult fish has mostly been approached from an aquatic toxicology perspective, focusing on reproductive disruption (Andersen et al, 2006; Hornung et al, 2004). Oral MT administration to adult male Dwarf Gouramis resulted in brighter coloration and increases in GSI (Biswas, Behera, Das, Meena, & Behera, 2014). Other studies have demonstrated changes in sexual phenotype using substances besides MT, such as other hormones or aromatase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…This is indicated by modeling results of the color intensity response without the control treatment and also the considerable separation in the “seller” coloration result among the MT diet concentrations at weeks 7–9 (Figure 3c). A previous study examined the effects of MT diet administration (0, 5 10, and 15 mg/kg for 90 days) on the coloration of adult male Dwarf Gouramis (Biswas et al, 2014). In this study, MT administration increased color intensity at all dosages.…”
Section: Discussionmentioning
confidence: 99%